Application and optimization of solid-state fermentation process for enhancing polygalacturonase production by Penicillium expansum - Zhu, Mingming; He, Hongju; Fan, Mingtao; Ma, Hanjun; Ren, Haiwei; Zeng, Jie; Gao, Haiyan (International Journal of Agricultural and Biological Engineering, 2018)
Penicillium expansum 3.5425 was applied in solid-state fermentation (SSF) of agricultural wastes for polygalacturonase biosynthesis. Among various carbon additives, apple pomace was most suitable for the biosynthesis of polygalacturonase (1440.57 U/g). Optimization of medium parameters using rotational orthogonal design (ROD) experiment combined with optimal fermentation conditions resulted in a 2.72-fold increase in the polygalacturonase production. By using ammonium sulphate precipitation, ion-exchange and gel-permeation chromatography, the polygalacturonase produced by P. expansum 3.5425 was finally purified which had specific activity of 19269 U/mg and molecular weight of 30 kDa. The enzyme was remarkably active in the pH range of 3-5 and at 50°C, which makes it more acceptable in the industrial application. Besides, partially purified polygalacturonase (875.15 U/mL) was used for apple juice clarification and the clarity at 0.4 mL/kg was maximum, which reveals a great potential of polygalacturonase in food industry.Keywords: solid-state fermentation (SSF), polygalacturonase, Penicillium expansum, juice clarification, agricultural wastesDOI: 10.25165/j.ijabe.20181106.3673Citation: Zhu M M, He H J, Fan M T, Ma H J, Ren H W, Zeng J, et al. Application and optimization of solid-state fermentation process for enhancing polygalacturonase production by Penicillium expansum. Int J Agric & Biol Eng, 2018; 11(6): 187–194.